Issues and Problems Faced by Rural Farmers in Paddy Cultivation: A Case Study of the Iban Paddy Cultivation in Kuala Tatau, Sarawak - Daniel Ugih Echoh; Norizan Md Nor; Salfarina Abdul Gapor; Tarmiji Masron (P4W LPPM IPB, 2017)
Rice is an important staple food in Asia. However, modernization and rapid development have reduced and threatened the practice, especially maintaining traditional hill rice cultivation, as in this case study by the Iban in Kuala Tatau located in the largest state in Malaysia, called Sarawak. It is important to understand the problems and challenges of this issue to ensure food security among the rural population in Sarawak, particularly the Iban. Therefore, this paper aims to discuss the issues and problems faced by rice farmers in Kuala Tatau, Sarawak. The respondents were Iban farmers in Kuala Tatau; named Sungai Semanok and Kuala Serupai, were selected as it is at a great distance from urban areas named Bintulu, and they still practices paddy cultivation. For the purpose of obtaining the data, qualitative research methods through in-depth interview techniques, group discussion and observation were utilized and the data were analyzed using content analysis. The results showed that the rice sector faced major problems such as the decrease of the number of farmers and a weak system in the distribution of subsidies. However, there were differences shown in results between the two villages as well, which were in term of inadequate agricultural land, and issues on drainage and irrigation system, depending on the distance of the village from urban area, transport facilities, and other issues as discussed in the following section.